Geometry, formation mechanisms, and hydrocarbon exploration significance of Pishan Caldera, Tarim Basin, northwest China. (4th March 2023) - Li, Meng; Yan, Xiangbin; Tang, Liangjie; Yun, Lu
Abstract: The discovery of an oil reservoir in Pishan Caldera of the Tarim Basin, northwest China, highlights the hydrocarbon exploration potential of large calderas. We used 3 D seismic interpretations, waveform clustering analysis, and seismic profiles to investigate the origin and evolution of Pishan Caldera, along with the mechanisms of hydrocarbon accumulation, and its significance for future oil and gas exploration. Pishan Caldera is located at depths of >7000 m, has an elliptical shape, extends over an area of 25 × 20 km, and is surrounded by ring faults. Pishan Caldera were the result of magma withdrawal and later magma intrusion. Volcanic eruptions, caldera collapse, and reactivation of Pishan Caldera resulted in Cretaceous oil migration and accumulation in Cretaceous breccia reservoirs. Ring faults, dense fracture networks, and lava tubes associated with the caldera acted as conduits for upward hydrocarbon migration. We propose a generalized model for hydrocarbon reservoirs related to the caldera, which includes five major reservoir types: drape anticline, fault block, volcanic-trapped, laterally sealed and lava tube type. Further efforts should be made to identify deep caldera structures that may be targets for hydrocarbon exploration.